Economic agglomeration potential and base: A location quotient, shift-share, and intersectoral backward-forward linkage analysis - Tazkiyah Ainul Qolbi (Journal of Economic Resilience and Sustainable Development, 2026)
Background: Agglomeration economy not only occurs in metropolitan cities, but can also developing in various other regions that have potential economy. Every area own potential for form agglomeration economy as effort create centers industry new. Methods: This study uses secondary data in the form of 2010 ADHK GRDP according to Business Fields 2019-2023 and Indonesia's Input-Output based on Transaction Domestic Based on Producer Prices According to Business Sector in 2016 and 2020. The GRDP variable is used For count Location Quotient (LQ) and Shift Share, while Input-Output data is used For analyzing Backward-Forward Linkage. Data analysis using device RStudio software. Findings: Period 2019-2023 shows​ transformation gradually going to economy agglomeration economy in the former region Banyumas Residency, with Purbalingga as the fastest diversification engine, Banyumas as knot service public and finance, Cilacap on logistics and accommodation which is increasingly strong, and Banjarnegara stable in agriculture with acceleration tourism. Furthermore, the analysis of sectoral linkages identifies a significant potential for current non-progressive sectors to transition into dynamic-base classifications through enhanced value-added integration. Conclusion: This study concludes that the Former Banyumas Residency is transitioning into a functional economic agglomeration where Purbalingga and Banjarnegara serve as essential upstream agricultural bases, while Cilacap and Banyumas act as downstream hubs for manufacturing and services. Novelty/Originality of this article: Novelty study This namely integration three method analysis regional economy. Temporal analysis of post-pandemic economic shift. Focus research in non-metropolitan areas, namely Former Residency Banyumas. Approach new in evaluate potential agglomeration sectoral.